Unlocking species identity: geometric morphometrics of head and thorax shapes in invasive and non-invasive quarantine-significant thrips (Thysanoptera: Terebrantia) - Smith-Pardo, Allan H.; Pérez, Laura M.; Benítez, Hugo A. (Frontiers in Insect Science, 2025)
This study use landmark based geometric morphometrics (GM) of the head and the thorax on eight species of thrips of the species-rich genus Thrips. Among the selected species, four were classified as common and not significant, while four were identified as quarantine-significant and agriculturally important in the USA. The results indicate the potential for using both sets of landmarks, which, in some cases, were complementary. When one set did not reveal significant differences in shape, the other provided valuable insights. The geometric morphometric analysis of the selected landmarks revealed statistically significant differences in head morphology and the configuration of setal insertion points on the mesothorax and metathorax. Principal component analysis (PCA) served as the primary method to examine the ordinal distribution of the eight species within the morphospace. The analysis highlighted T. australis and T. angusticeps as the most morphologically distinct species in terms of head shape, while T. nigropilosus, T. obscuratus, and T. hawaiiensis exhibited the greatest divergence in thoracic morphology. The results further demonstrate the potential of geometric morphometric (GM) methods for identifying taxa that are challenging to distinguish using traditional taxonomy based on external morphology. This is particularly relevant for morphologically conservative taxa, such as thrips with minimal or no wing venation (a feature often used in GM studies of winged insects), species complexes (e.g., T. hawaiiensis and related species examined in this study), and taxa exhibiting morphological similarity due to convergent evolution associated with shared ecological niches.